Space Radiation and Plasma Effects on Satellites and Aviation: Quantities and Metrics for Tracking Performance of Space Weather Environment Models. Issue 10 (15th October 2019) - Zheng, Yihua; Ganushkina, Natalia Yu; Jiggens, Pier; Jun, Insoo; Meier, Matthias; Minow, Joseph I.; O'Brien, T. Paul; Pitchford, Dave; Shprits, Yuri; Tobiska, W. Kent; Xapsos, Michael A.; Guild, Timothy B.; et al.
Abstract: The Community Coordinated Modeling Center has been leading community‐wide space science and space weather model validation projects for many years. These efforts have been broadened and extended via the newly launched International Forum for Space Weather Modeling Capabilities Assessment (https://ccmc.gsfc.nasa.gov/assessment/ ). Its objective is to track space weather models' progress and performance over time, a capability that is critically needed in space weather operations and different user communities in general. The Space Radiation and Plasma Effects Working Team of the aforementioned International Forum works on one of the many focused evaluation topics and deals with five different subtopics (https://ccmc.gsfc.nasa.gov/assessment/topics/radiation‐all.php ) and varieties of particle populations: Surface Charging from tens of eV to 50‐keV electrons and internal charging due to energetic electrons from hundreds keV to several MeVs. Single‐event effects from solar energetic particles and galactic cosmic rays (several MeV to TeV), total dose due to accumulation of doses from electrons (>100 keV) and protons (>1 MeV) in a broad energy range, and radiation effects from solar energetic particles and galactic cosmic rays at aviation altitudes. A unique aspect of the Space Radiation and Plasma Effects focus area is that it bridges the space environments, engineering, and user communities. The intent of the paper is to provide an overview of the current status and to suggest a guide for how to best validate space environment models for operational/engineering use, which includes selection of essential space environment and effect quantities and appropriate metrics. Plain Language Summary: In order to track space weather models' progress and performance over time, user‐focused metrics using proper physical quantities are critically needed. This paper summarizes the working team's initial efforts of defining two types of interlinked physical quantities from both science and engineering perspectives in the subject of space radiation and plasma effects on space assets. Key Points: Providing an overview of the current status and proposing a guide for how to best validate space environment models for operational use Two types of physical quantities for both science and engineering purposes have been identified Proper metrics are needed for evaluating space environment models for different application purposes